Community Awareness in Household Waste Management - Affila; Afnila; Devi, T.Keizeirina (Talenta Publisher, 2020)
Â Garbage is the final waste from a production activity and household activities in general. Garbage is a big problem faced by every country. Garbage if not managed and handled will cause various problems to the environment and for humans themselves. The presence of garbage has a bad impact and has become a threat to the survival of all mankind. Waste is generated by human activities, therefore awareness and the role of humans in overcoming and overcoming it becomes important.